ENVIRONMENTAL PROTECTION IN THE LIGHT OF DISCREPANCY BETWEEN THE NORMATIVE AND THE REALITY - Počuča, Milan; Joksić, Ivan; Drašković, Bojana (Economics of Agriculture, 2018)
The work is a synthesis of three important aspects in the approach to the environment, on the basis of which it is possible to meet its normative defnition and understanding of the situation in practice. Given this basis it is possible to separate international, general and criminal legal area of its normative regulation. Each of these aspects is equally important in getting to know the area of the environment in our country. Hence, it is used in expanding the methodological approach which comprises a number of methods (legal, social, statistically, systematically et al.). In addition to the theoretical part of the work an important aspect is the research pertinent to scope and dynamics of criminal acts against the environment in the country. The results are tabulated on the basis of which conclusions are derived as well as suggestions de le ferenda. Timeframe of the research covers the period 2011-2015. year and is based on information contained in the bulletins RSO. We believe that the fve-year period in determining the oscillating trends in the feld of criminal law protection of the environment provides suffcient referral. In the fnal part of the paper, a detailed analysis of material is presented as well as a critical review of the presence of inconsistency between the normative and the real situation in the feld of environmental protection.